Answer:
1
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
x+24+13=2x−16
x+ 1 2 + 1 3 =2x+ −1 6
(x)+( 1 2 + 1 3 )=2x+ −1 6 (Combine Like Terms)
x+ 5 6 =2x+ −1 6
x+ 5 6 =2x+ −1 6
Step 2: Subtract 2x from both sides.
x+ 5 6 −2x=2x+ −1 6 −2x
−x+ 5 6 = −1 6
Step 3: Subtract 5/6 from both sides.
−x+ 5 6 − 5 6 = −1 6 − 5 6
−x=−1
Step 4: Divide both sides by -1.
−x −1 = −1 −1
x=1
Trapezoid ABCD was the original figure for trapezoid A'B'C'D. They are similar because they are the same shape, Trapezoid A'B'C'D is slightly bigger or smaller because it was dilated from trapezoid ABCD.
i)
Pythagorean's theorem: √50
j)
Pythagorean's theorem: √1/2
Answer: 18
Step-by-step explanation:
1/4 of 32 = 8
8+10 = 18
My teachers desk would fit about 6 1/2